59 ATORVASTATIN ATTENUATES LRP5/WNT-MEDIATED ATHEROSCLEROSIS AND OSTEOPOROSIS IN A MOUSE MODEL OF EXPERIMENTAL HYPERCHOLESTEROLEMIA. (1st March 2007) - Rajamannan, N. M.; Subramaniam, M.; Caira, F. C.; Stock, S.; Hefferan, T.; Flores, A.; Spelsberg, T. C.
Abstract : Atherosclerosis and osteoprorosis are the leading causes of morbidity and mortality in the aging population in the United States. Evidence indicates that hyperlipidemia plays a paradoxical role in these disease processes. However, the hyperlipidemic mechanisms of atherosclerotic calcification and decrease bone mass are not well understood. We have previously shown that cardiovascular calcification expresses an Lrp5/Wnt-mediated osteoblast phenotype in humans. We hypothesize that hyperlipidemia plays a role in cardiovascular calcification and osteoporosis via reagulation of the Lrp5/Wnt pathway. We propose to test this hypothesis in an experimental hypercholesterolemia model and further test if statins play a protective role in this process LDLR −/− mice ( n = 60). Group I ( n = 20) normal diet, group II ( n = 20) 0.2% chol diet (w/w), and group III ( n = 20) 0.2% (w/w) chol diet + atorv for the development of calcification. The aortic valves and aortas (AVAs) were examined for proliferation, calcification, Lrp5/Wnt, and bone matrix markers. Bone formation was assessed by micro-computed tomography (microCT), calcein injection, osteocalcin, and cbfa-1 and osteopontin expression. Results: The cholesterol diet induced complex bone formations by microCT in the calcified aortic valves and aortas with an increase in cellular proliferation, osteopontin, osteocalcin, Lrp5, and cbfa-1 expression. Atorvastatin reduced bone formation, cellular proliferation Lrp5, and cbfa-1 levels in the AVAs. Ex vivo analysis of calcein label demonstrated an increase in calcein in the hypercholesterolemia AVAs and bones with attenuation of the label with atorvastatin in these tissues. The cholesterol-treated femurs demonstrated an increase in bone resorption, with a decrease in Lrp5/Cbfa1. The cholesterol-treated femurs demonstrated an increase in calcein incorporation. Conclusion: Hypercholesterolemic AVA calcification and bone turnover are attenuated by atorvastatin and are mediated in part by an Lrp5/Wnt pathway. This model may have future implications in the treatment of cardiovascular calcification and osteoporosis with statin therapy.